2016
DOI: 10.1002/prep.201600007
|View full text |Cite
|
Sign up to set email alerts
|

Mn+Sb2O3 Thermite/Intermetallic Delay Compositions

Abstract: Abstract:The binary Mn + Sb 2 O 3 pyrotechnic composition was investigated for mining detonator time delay applications. EKVI thermodynamic modelling predicted two maxima in the adiabatic reaction temperature. The local maximum, at a manganese fuel content of ca. 36 wt-%, corresponds to a pure thermite-type redox reaction: 3Mn + Sb 2 O 3  3MnO + 2Sb. The overall maximum in the adiabatic reaction temperature (ca. 1640 K), at the fuel-rich composition of 49 wt-% Mn, is consistent with the reaction 5Mn + Sb 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The thermochemistry for the reaction of Mn with Sb 2 O 3 was previously reported [13]. The normal redox reaction: 3Mn + Sb 2 O 3 !3MnO + 2Sb dominates in fuel-lean mixtures.…”
Section: Thermochemistrymentioning
confidence: 85%
“…The thermochemistry for the reaction of Mn with Sb 2 O 3 was previously reported [13]. The normal redox reaction: 3Mn + Sb 2 O 3 !3MnO + 2Sb dominates in fuel-lean mixtures.…”
Section: Thermochemistrymentioning
confidence: 85%
“…Manganese/antimony trioxide. EKVI thermodynamic modelling predicted two maxima in the adiabatic reaction temperature for the binary Mn/Sb 2 O 3 pyrotechnic system [90].…”
Section: Manganese As Fuelmentioning
confidence: 99%
“…Dugam et al [74] investigated the effect of particle size distributions and found higher packing densities for wider distributions of oxidant particle sizes and lower packing densities when the fuel and oxidant particles have similar sizes. Montgomery et al [90] investigated the effect of particle packing through variations in fuel to oxidant particle size ratios. The particle packing was found to be unaffected by the volumetric ratio of the fuel to oxidant particles.…”
Section: Particle Size Particle Size Distribution and Particle Shapementioning
confidence: 99%
See 2 more Smart Citations